Branched poly (lactic acid) microparticles for enhancing the 5-aminolevulinic acid phototoxicity - Di Martino, Antonio; Trusova, Marina E; Postnikov, Pavel S; Sedlarik, Vladimir (Journal of photochemistry and photobiology. B, Biology, 2018)
An innovative microcarrier based on a carboxy-enriched and branched polylactic acid derivative was developed to enhance the in vitro phototoxicity of the photosensitizer and prodrug 5-aminolevulinic. Microparticles, prepared by double emulsion technique and loaded with the prodrug were carefully characterized and the effect of the polymer structure on the chemical, physical and biological properties of the final product was evaluated. Results showed that microparticles have a spherical shape and ability to allocate up to 30 μg of the photosensitizer per mg of carrier despite their difference in solubility. Release studies performed in various simulated physiological conditions demonstrate the influence of the branched structure and the presence of the additional carboxylic groups on the release rate and the possibility to modulate it. In vitro assays conducted on human epithelial adenocarcinoma cells proved the not cytotoxicity of the carriers in a wide range of concentrations. The hemocompatibility and surface proteins adsorption were evaluated at different microparticles concentrations to evaluate the safety and estimate the possible microparticles residential time in the bloodstream. The advantages, of loading 5-aminolevulinic acid in the prepared carrier has been deeply described in terms of enhanced phototoxicity, compared to the free 5-aminolevulinic acid formulation after irradiation with light at 635 nm. The obtained results demonstrate the advantages of the prepared derivative compared to the linear polylactide for future application in photodynamic therapy based on the photosensitizer 5-aminolevulinic acid.
Keywords: HeLa Cells; Cell Line, Tumor; Hydrogen-Ion Concentration; kyselina aminolevulová; erytrocyty; hemolýza; Drug Carriers; lidé; HeLa buňky; Photosensitizing Agents; Solubility; Drug Liberation; rozpustnost; Polyesters; fotosenzibilizující látky; Light; Erythrocytes; Hemolysis; nosiče léků; Aminolevulinic Acid; Cell Survival; světlo; uvolňování léčiv; viabilita buněk; polyestery; koncentrace vodíkových iontů; nádorové buněčné linie; Humans